2019
DOI: 10.26508/lsa.201900516
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous epitope-tagging of Tet1, Tet2 and Tet3 identifies TET2 as a naïve pluripotency marker

Abstract: Tet1, Tet2, and Tet3 encode DNA demethylases that play critical roles during stem cell differentiation and reprogramming to pluripotency. Although all three genes are transcribed in pluripotent cells, little is known about the expression of the corresponding proteins. Here, we tagged all the endogenous Tet family alleles using CRISPR/Cas9, and characterised TET protein expression in distinct pluripotent cell culture conditions. Whereas TET1 is abundantly expressed in both naïve and primed pluripotent cells, TE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 44 publications
2
18
0
Order By: Relevance
“…We reconstructed GRNs for 2iL and SL condition separately and compared the regulators as well as their specific targets ( Supplementary Figure S12 ; see ‘Materials and Methods’ section). We found several naïve pluripotency markers specifically enriched in 2iL condition including Nanog ( 56 ), Esrrb ( 57 ) and Tfcp2l1 ( 58 , 59 ), whereas heterogeneous and hypermethylated SL condition ( 60 , 61 ) regulators included Tet1 ( 62 , 63 ) and Dnmt3l ( 64 ) and Zfp57 ( 65 ) ( Supplementary Figure S12 ). Interestingly, Nme2 was a top mESC regulator for the 2iL GRNs.…”
Section: Resultsmentioning
confidence: 99%
“…We reconstructed GRNs for 2iL and SL condition separately and compared the regulators as well as their specific targets ( Supplementary Figure S12 ; see ‘Materials and Methods’ section). We found several naïve pluripotency markers specifically enriched in 2iL condition including Nanog ( 56 ), Esrrb ( 57 ) and Tfcp2l1 ( 58 , 59 ), whereas heterogeneous and hypermethylated SL condition ( 60 , 61 ) regulators included Tet1 ( 62 , 63 ) and Dnmt3l ( 64 ) and Zfp57 ( 65 ) ( Supplementary Figure S12 ). Interestingly, Nme2 was a top mESC regulator for the 2iL GRNs.…”
Section: Resultsmentioning
confidence: 99%
“…This exciting possibility remains to be addressed. On the other hand, we and others have shown that TET1 and TET2 not only display specific patterns of expression in defined pluripotent subtypes (Fidalgo et al, 2016 ; Pantier et al, 2019 ; Mulholland et al, 2020b ), but most importantly, play opposite roles in regulating naïve and primed pluripotency (Fidalgo et al, 2016 ). While TET1 is important for primed pluripotency, TET2 is a key determinant of naïve one.…”
Section: An Expanded View Of Tet2 In Pluripotency In Vitro mentioning
confidence: 84%
“…Interestingly, one of the NANOG-interaction domains (1522-1547) includes residues that interact with DNA, that lie adjacent to the TET1 catalytic domain and that are conserved in TET2 and TET3 [58]. We have recently identified two binding regions in TET2 that interact with NANOG and one of these includes residues homologous to TET1 1522-1547 [21]. Importantly, this region (1522-1547) also contains residues that bind methylated CpG [58].…”
Section: Tet1mentioning
confidence: 99%
“…TET protein activity is required both for proper differentiation [14,15] and reprogramming to pluripotency [16][17][18]. TET1 is the most highly expressed TET family protein both in pluripotent cells and during early development [19][20][21]. TET1 predominantly binds to promoters via its N-terminal CXXC domain which recognises unmethylated CpG dinucleotides [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%